STUDENTS’ CHALLENGES IN LEARNING ENGLISH THROUGH INDUSTRIAL REVOLUTION ERA 5.0 USING QUIPPER APPLICATION - Putri Nabilah Maharani; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2023)
This study focuses on the challenges faced by students learning English during the era of the Industrial Revolution. It has two main objectives: 1) to explore how teachers implement the Quipper application for English instruction in the context of Industrial Revolution 5.0; and 2) to identify the challenges experienced by both students and teachers. The research adopts a qualitative descriptive approach, employing observation, interviews, and documentation as data collection methods. The analysis of the findings indicates that the teacher effectively utilises the Quipper application as a teaching tool for English, aligning with lesson plans and previous studies. The challenges faced by students and teachers in the industrial revolution era are influenced by various internal and external factors, particularly the level of interest and motivation. These factors can affect both students and teachers alike. Additionally, a slow internet connection emerges as a significant challenge not only for students but also for teachers in the teaching-learning process during the era of Industrial Revolution 5.0.